Analisis Pengaruh Suhu Lingkungan Terhadap Kinerja dan Hasil Produksi Mesin Es Maker ICB-2000P - Fajrin; Tamaji (Universitas Widya Kartika Surabaya, 2024)
The increasing demand for ice across various sectors, such as the food, beverage, and hospitality industries, is driven by changes in modern lifestyles and extreme weather conditions, particularly during dry seasons. This study aims to explore the impact of ambient temperature on the performance of the ICB-2000P ice maker. The research was conducted in Penajam Paser Utara Regency from October 1 to 2, 2024, utilizing temperature measurement tools and electric current meters. The results indicate that lower ambient temperatures (below 30 degrees Celsius) enhance ice production efficiency, with total production reaching 213.72 kg compared to 89.05 kg at temperatures above 30 degrees Celsius. Additionally, electricity consumption also increased at higher temperatures, rising from 5262 VA to 5525 VA. Thus, this study underscores the importance of managing room temperature to optimize the performance of ice makers. Recommendations for improving air circulation and using insulation are expected to enhance ice production efficiency and reduce operational costs in the long term.